Chapter: 'The Booth: Bringing Out the Super Hero in You' from book: Adaptive and Adaptable Learning: 11th European Conference on Technology Enhanced Learning, EC-TEL 2016, Lyon, France, September 13-16, 2016, Proceedings - Dirk Börner; Peter van Rosmalen; Jan Schneider; Marcus Specht (Springer Nature, 2016)
The acquisition of knowledge is a key aspect for learners. However, in moments of stress the cognitive capacities of learners decrease considerably, making it very difficult for learners to get access and use their already acquired knowledge. Therefore we developed The Booth, a prototypical toolkit designed to support learners to prepare for key situations that are foreseen to be stressful. It guides the learner through a series of lectures helping them to gain personal power, and become in touch with their sincere-self. This paper presents the prototype, including the description of its technical aspects and the theory behind its lectures.
English
Keywords: affective computing; self-confidence; demonstration; sensor-based learning